Preparation and application of an electronic distribution board game as a tool for improving chemistry teaching learning (Research, Society and Development, 2022)
The creation of fun games to facilitate student learning is very important when it comes to complementing theoretical classes and reinforcing learning, making it more meaningful. Board games are widely used in different areas of knowledge and help students from different courses, and can be used as a new teaching methodology. Your application can contain several subjects related to the content applied in the classroom, where students can learn in a fun way and memorize easily. This work aimed to develop a board game, addressing the subject of electronic distribution, to be used with the students of the Campus IFCE Caucaia. This board applies knowledge of electronic distribution in a playful way and quickly and practically addresses other knowledge such as: volumetric properties, density and boiling point. The game was designed using card models, where the player must follow the rules of the game's methodology, completing each step through a chemical roulette wheel. The game managed to achieve its objective, in its application, in the classroom, contributing to the improvement of learning and encouraging students to use the previous knowledge acquired, relating them to everyday life.